Terra adorada, mãe gentil: representações do feminino e da natureza no Brasil da Era vargas, 1930-1945 - Natascha Stefania Carvalho Ostos (2009)
This study proposes to examine the emergence in Brazil's Vargas Age (1930-1945) of a strong society concern and a established power with knowledge production, practices and rules that regulate population's life in its biological aspects, including birth phenomena, reproduction and health in order to integrate human potential into material territory conditions. The state is regarded as the great social relations manager, responsible for promoting the physical wellbeing of Brazil and at the same time boost the country economic forces through natural resources exploitation. In the context of concerns involving life development and measures related to public health, birth rate, nutrition and population longevity the woman figure had fundamental importance. To form a healthy nation the women needed education in modern principles of life conservation, because they were responsible to ensure them at home together with preventive medicine principles, nutrition and psychology. In nature itself she incarnated not only the very possibility of sustaining life, but also the promise of economic growth through richness exploitation. In this sense, both women and nature were represented as signs of life, affirming principles of abundance and fertility, similar to those ideals that Vargas government wanted to build the Brazilian nation, land of abundance, productivity and economic strength.